Impact of HIV infection and highly active antiretroviral therapy (HAART) on B cell subpopulations in children. Issue 7 (6th April 2018) - Singh, Ravinder; Mukherjee, Aparna; Singla, Mohit; Vajpayee, Madhu; Negi, Neema; Kabra, Sushil K.; Lodha, Rakesh; Das, Bimal K.
Abstract : B‐cells play an important role in defending children against various infections. In view of scare data, we undertook this prospective cohort study to describe B cell compartment in HIV infected children (<5 years of age) and the effect of HAART on B cell subpopulations. HIV infected children (<5 years) from Pediatric HIV services of the Department of Pediatrics, All India Institute of Medical Sciences, New Delhi, were recruited (April 2012‐December 2015). The enrolled HIV‐1 infected children ( n = 59) were followed up regularly for 12 months; healthy controls ( n = 51) included HIV uninfected children with no major illness. Flow cytometry was performed on fresh EDTA‐treated blood samples to characterize B cell subpopulations. In HIV‐infected children, marked depletion of naive ( P = 0.003), non‐switched memory ( P = 0.02), mature ( P = 0.0005), resting memory ( P < 0.0001) B cells, and expansion of double negative memory ( P < 0.0001), activated memory ( P < 0.0001) and tissue like memory ( P < 0.0001) B cells were observed as compared to healthy controls. In children started on HAART, at the end of 12 months of therapy, frequencies of non‐switched memory ( P = 0.04), switched memory ( P = 0.01), and resting memory ( P = 0.003) B cells were lower; activated memory ( P = 0.04), and tissue‐like memory ( P = 0.0001) B cells were still higher than healthy controls. HIV infection resulted in reduced memory B cells in HIV infected children. Following HAART, there was normalization of some B cell subpopulations. The study emphasizes the need of re‐vaccination in HIV infected children to maintain the memory B cell pool and adequate humoral immune response against infections.